Inheritance of resistance to leaf rust (Pueeinia reeondita f.sp. tritiei) in five bread wheat cultivars - ANUJ KUMAR and RAM CHARAN, P. BAHADUR, DINESH SINGH, (Indian Phytopathology, 2002)
Five bread wheat cultivars i.e., HD 2643, ill 1077, lIP 1731, UP 2338 and WH 147 resistant to leaf rust (Puccinia recondita f.sp. tritici), were crossed with susceptible cultivar Agra Local. Reciprocal and diallele crosses were also attempted to evaluate the inheritance of resistance. The studies were conducted with 2 virulent and prevalent pathotypes 77-2 (109R31-1) and 104-2 (21R55) and one most avirulent pathotype 106 (OR9)of P. recondita f.sp. tritici using the parents, F. and F2 plants and BC.F2and BC2F2families. Three independent dominant resistance genes in HD 2643, two dominant independent genes for resistance each in ill 1077 and WH 147 and two dominant independent and one recessive gene each in lIP 1731 and UP 2338 were identified. Reciprocal crosses of above cuItivars and analysis of BC.F2and BC2F2have confirmed the above findings.